2013
DOI: 10.1242/jcs.122531
|View full text |Cite
|
Sign up to set email alerts
|

Control of Sty1 MAPK activity through stabilisation of the Pyp2 MAPK phosphatase

Abstract: SummaryIn all eukaryotes tight control of mitogen-activated protein kinase (MAPK) activity plays an important role in modulating intracellular signalling in response to changing environments. The fission yeast MAPK Sty1 (also known as Spc1 or Phh1) is highly activated in response to a variety of external stresses. To avoid segregation of damaged organelles or chromosomes, strong Sty1 activation transiently blocks mitosis and cell division until such stresses have been dealt with. MAPK phosphatases dephosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…6A). To ensure accurate quantification, three separate samples were analyzed by using Ponceau S staining as the loading controls (41). We found that Rad3 in tel2-C307Y cells was reduced to 60.1% Ϯ 1.3% (n ϭ 3) of the wild-type level (Fig.…”
Section: Elimination Of Rad3 Phosphosignaling In the Drc Under Replimentioning
confidence: 93%
“…6A). To ensure accurate quantification, three separate samples were analyzed by using Ponceau S staining as the loading controls (41). We found that Rad3 in tel2-C307Y cells was reduced to 60.1% Ϯ 1.3% (n ϭ 3) of the wild-type level (Fig.…”
Section: Elimination Of Rad3 Phosphosignaling In the Drc Under Replimentioning
confidence: 93%
“…Alkaline phosphatase coupled secondary antibodies were used for all blots, followed by direct detection with NBT/BCIP (VWR International Ltd.) substrates on PVDF membranes (Millipore). Ponceau S staining was used as a loading control [ 63 ]. Relative protein levels were quantified in ImageJ and GraphPad Prism was used to calculated significant differences.…”
Section: Methodsmentioning
confidence: 99%
“…TCCACTCTTCAAGCCTCGTA TAGAAGAAAAGGCAGAGGCT rsv1- (5) CTAGCGCTGGTCTCTTCATT TGGAAACAAGTAAACGCCCG rsv1- (6) CTTCCCCCACAATCTTAATTC AGTGGAAAAGGCCGATTCCA rsv1- (7) CTTGCAAGCCCAATCTAAGC CGCCTGCTGATTCTGAAATAG rsv1- (8) TGAGGTAACATTTCCGCAGC GACGAAGAGGGTAAACGAAAC rsv1- (9) ACGTCCTCGGAAATCCAACT CGCCGTTAGTGTGAAATGAAG gcd1…”
Section: Protein Preparation and Western Blottingmentioning
confidence: 99%
“…Similar to the high-osmolarity glycerol pathway in budding yeast, which is activated by several stresses, Abbreviations bZIP, basic leucine zipper; EGFP, enhanced green fluorescent protein; MAPK, mitogen-activated protein kinase; PKA, protein kinase A. the MAPK protein Sty1, a S. pombe homolog of Hog1, responds to many different environmental stresses, such as high osmolarity, oxidation, heat shock, and nutrient depletion, and plays a crucial role in cell survival [4][5][6]. Atf1, the main effector protein of Sty1, is normally localized to the nucleus and is directly phosphorylated by activated Sty1 under stress conditions [7].…”
Section: Introductionmentioning
confidence: 99%